2019
DOI: 10.1590/1980-5373-mr-2019-0189
|View full text |Cite
|
Sign up to set email alerts
|

ToF-SIMS Characterization of Nanostructured ZrO2 Coatings Applied to Near Equiatomic Ni-Ti Alloy

Abstract: The ToF-SIMS technique was applied to analyze thin ZrO 2 coatings deposited on the surface of a Ni-Ti alloy. Due to its nanostructured nature, these films are difficult to characterize by conventional techniques. ZrO 2 coatings were deposited on near equiatomic Ni-Ti wires by pulse electrodeposition. Part of the samples was electrolytically polished before the coating process. The coated samples were then analyzed by ToF-SIMS to evaluate the influence of the deposition time and previous surface electropolishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…As reported by Solheid et al [43], during the laser polishing process, high temperatures occur on the polishing zone at the surface of the workpiece and can create extended areas of heat-affected tissue with resulting microstructural changes that significantly influence the biocompatibility of a thin stent wire. Lopes et al [44] have found problems with ZrO 2 coatings, particularly that the production of ZrO 2 nano-coatings is difficult due to their reduced dimensions. Moreover, this process requires long processing for up to 1200 s to achieve NiTi stent wires with smooth surfaces, greatly increasing the costs to produce these products.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by Solheid et al [43], during the laser polishing process, high temperatures occur on the polishing zone at the surface of the workpiece and can create extended areas of heat-affected tissue with resulting microstructural changes that significantly influence the biocompatibility of a thin stent wire. Lopes et al [44] have found problems with ZrO 2 coatings, particularly that the production of ZrO 2 nano-coatings is difficult due to their reduced dimensions. Moreover, this process requires long processing for up to 1200 s to achieve NiTi stent wires with smooth surfaces, greatly increasing the costs to produce these products.…”
Section: Introductionmentioning
confidence: 99%